Legal Problems Arising from the Extension of the Insolvency of a Partnership Company to its Partners: An Analytical Study in the Light of Jordanian Companies and Insolvency Laws - Al-Kharabsheh, Sami Mohammad; Alghathian, Ghazi Ayed (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This study evaluated how the Companies Law aligns with the 2018 Insolvency Law standards concerning the insolvency of general partnership partners when the partnership is declared insolvent. It also analyzed whether the Jordanian legislator established specific procedures for extending a partnership’s insolvency to its partners and assessed the amended 2023 Companies Law’s applicability to active, withdrawn, and deceased partners in insolvency proceedings. Method: The study used an analytical approach, comparing the amended Companies Law No. 20 of 2023 with the Jordanian Insolvency Law No. 21 of 2018. It aimed to recommend solutions for legal issues related to extending partnership insolvency to partners. The study was divided into two sections: one examining the extension of a partnership’s insolvency to its partners and another addressing the legal implications of partner insolvency due to the partnership’s insolvency. Results: The legal basis for extending the declaration of a general partnership’s insolvency to its partners stems from the Companies Law as a specific law governing this issue, rather than the Insolvency Law, which generally addresses insolvency matters. The amendments introduced by the Jordanian legislator in the 2023 Companies Law are insufficient to comprehensively address the legal and procedural issues associated with extending partner insolvency arising from the partnership’s insolvency. Conclusion: The insolvency of a general partnership affects its partners, particularly in procedures, timing, and the unification of insolvency estates. The study urges the Jordanian legislator to amend laws to address all aspects of partner insolvency following a partnership’s insolvency.